How can health be further integrated in urban development policymaking in the United Kingdom? A systems mapping approach - Geoff Bates; Pablo Newberry; Rachael McClatchey; Jack Newman; Sarah Ayres (Health Research Policy and Systems)
Abstract Background In the United Kingdom the government’s new health mission aims to reduce the burden on healthcare services by shifting from treating poor health to prevention. Delivering this requires action on health in policy arenas outside of the health sector such as urban development, as urban environments are key health determinants. However, change is challenging in complex and long-established policy systems and structures. Systems methods can enhance research into such contexts and demonstrate opportunities for delivering cross-cutting preventative health agendas. Methods This study aimed to enhance understanding of how health is integrated in urban development policymaking, and how to bring about change to support healthier development. It was undertaken over two stages. Firstly, a thematic analysis of data from interviews with 37 United Kingdom policy officials exploring urban development decision-making in central government. Secondly, the development of a causal loop diagram based on the variables and connections between them, identified in the interview data. Results Analysis revealed how health is not well integrated in urban development policymaking. Through mapping 15 important influencing variables, we identified four main areas where change can be delivered: senior leadership on preventative health, responsibility in urban development teams for health, opportunities in urban development for health experts to promote ideas, and the capacity and capability of officials to act. Addressing any of the factors identified will likely have benefits, but it is by bringing change to multiple highlighted areas that health integration will be maximized. Conclusions If the United Kingdom Government’s health mission is to be effective, policymakers must be empowered and incentivized to act on health in areas such as urban development. There is recent evidence of enhanced leadership on health prevention, but this must be supported in in several ways simultaneously, with increased funding, facilitating joined up working across sectors, and enhancing the use of tools and evidence to understand and promote health outcomes. By taking a systems approach this study adds value to existing understandings by going beyond isolated challenges and opportunities, to illustrate the connections between them and, therefore, how any changes are likely to have wider effects.